Campus High-risk Drinking Culture as a Social Justice Issue: A Commentary on the Potential Impact on the Mental Health and Well-being of Marginalized College Students. Issue 4 (4th July 2017) - Satinsky, Sonya; Washington, Reonda L.; Pastor, Jonathan; Wagner, A. Katherine
ABSTRACT: High-risk drinking (HRD) is a public health priority on college campuses in order to decrease harm to individuals who engage in HRD, as well as others in their presence. We posit an underexplored impact of campus HRD culture: the exposure of marginalized students to instances of bias perpetrated by those under the influence. Therefore, our focus on the reduction of HRD is not just about the health of drinkers but is also about the dynamics of interpersonal factors and community-level factors that can be upstream determinants of chronic stress and illness, particularly for marginalized college students. We argue that more attention should be paid to the intersection of HRD and intersections with social justice violations. Furthermore, we propose a model based on existing research that connects HRD with incidents of bias that increase stress, thereby negatively impacting well-being and increasing risk for chronic mental and physical illness. We ask our colleagues to incorporate these effects into their data collection, programming, prevention and treatment priorities, and allocation of efforts. Adding a social justice lens to HRD prevention and treatment on campuses expands our ability to ensure that all members of our diverse, inclusive communities thrive while on campus and throughout their lives.